Appraisal of individual hydrogen bond strengths and cooperativity in ammonia clusters via a molecular tailoring approach. Issue 32 (9th August 2021) - Ahirwar, Mini Bharati; Patkar, Deepak; Yadav, Itee; Deshmukh, Milind M.
Abstract : In this work, we propose and test a method, based on the molecular tailoring approach (MTA), for the evaluation of individual hydrogen bond (HB) energies in ammonia (NH3 ) n clusters. Abstract : In this work, we propose and test a method, based on the molecular tailoring approach (MTA), for the evaluation of individual hydrogen bond (HB) energies in ammonia (NH3 ) n clusters. This methodology was tested, in our earlier work, on water clusters. Liquid ammonia being a universal, non-aqueous ionizing solvent, such information of individual HB strength is indispensable in many studies. The estimated HB energies by an MTA-based method, in (NH3 ) n for n = 3–8, were calculated to be in the range of 0.65 to 5.54 kcal mol −1 with the cooperativity contribution falling between −0.54 and 1.88 kcal mol −1 both calculated at the MP2(full)/aug-cc-pVTZ level of theory. It is seen that the strong HBs in (NH3 ) n clusters were additionally strengthened by the large contribution of HB cooperativity. The accuracy of these estimated HB energies was validated by approximately estimating the molecular energy of a given cluster by adding the sum of HB energies to the sum of monomer energies. This approximately estimated molecular energy of a given cluster was found to be in excellent agreement with the actual calculated values. The negligibly small difference (less than 5.6 kcal mol −1 ) in these two values suggests that the estimated individual HB energies in ammonia clusters are quite reliable. Furthermore, these estimated HB energies by MTA are in excellent qualitative agreement with the other indirect measures of HB strength, such as HB bond distances and angles, N–H stretching frequency and the electron density values at the (3, −1) bond critical points.